Development of a solution for simulating configurable real-time network responses - Cai, Yongkang (Nanyang Technological University, 2023)
Backend Engineers (BE) have the great fortune of using powerful interface testing tools such as Postman. Postman is a tool that can help BE to isolate their servers to remove any reliance on external dependencies, such as depending on frontend servers to initiate network request. It has become an essential tool for a backend engineer. Frontend Engineers (FE), however, has yet to receive a similar revolution in the way they develop their frontend servers. The idea that frontend must depend on backend is taken for granted. This project fundamentally argues for a shift in paradigm for FE, to isolate their frontend servers to remove any reliance on external dependencies. For example, frontend servers rely on backend servers to provide a network response during development phase. This reliance should be replaced by a well-rounded tool like Postman but meant for FE. This project presents the solution to remove this reliance, a tool named ‘MicMicProxy’ (MMP). It provides an elegant and intuitive way to simulate network responses for frontend servers. It can boost FE efficiency in every stage of the software development lifecycle, from development phase to quality assurance testing phase to being used in reproducing and fixing bugs. Moreover, MMP will be open-sourced and has a strong emphasis on developer experience to attract and enable potential contributors to help improve this project in the long run.